PENGARUH KADAR TROMBOSIT, HEMATOKRIT, HEMOGLOBIN DARAH DAN PROTEIN URIN PADA IBU PREEKLAMSI /EKLAMSI TERHADAP NILAI APGAR BAYI YANG DILAHIRKAN - Kawuryan, Siti Lintang (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT Preclapmsi or eclampsia is one of the risk factor for asfiksia on newborn that can predicted by lower Apgar score. The aim of this research  is  to  know  the  influence  of  the  trombocyte,  hematokrit,  hemoglobin,  and  urinary  protein  examination  of  preclampsi  or eclampsi mother to baby’s Apgar score. This research was a diskriptive-cross sectional retrospective study with Chi- square test, Fisher test x2 for trend statistic analysis. Total sample was 100 which choosen by simple random sampling. The parameter of this study was trombocyte, hematokrit, hemoglobin, and urinary protein examination of preclampsi or eclampsi mother and baby’s Apgar score. There was a significant influence relationship between the raise of blood hematocrit (p=0,0243), the decrease of the blood trombocyte (p= 0,0175) and the high level of proteinuria (p=0,0154) of preclampsi or eclampsi mother  to baby’s Apgar score. In the other hand, hemoglobin (p =0,3589), SGOT (p=0,5447),SGPT (p= 0,4850), Ureum (p = 0,1964), kreatinin (p= 0,3415) level was not significantly influence. The conclusion of this reseach is hematokrit ≥ 38 % and urinary protein ≥ 4+ on preclampsi or eclampsi mother are usefull for predicting lower Apgar score of the neonate with relative risk 7,609. Keyword: preclampsi or eclampsi, trombocyte, hematokrit, hemoglobin, and urinary protein examination, Agar score